Survey on the Viewpoints of Credit Beneficiaries Qua Consumers in Order to increase Banking Accountability - Dragoş Ilie; Laura Ungureanu (Amfiteatru Economic)
The paper aims to demonstrate that the unprecedented granting of consumer credits to population in recent years, under the circumstances of a spectacular goods supply growth, has adversely affected some consumers, and jeopardized the protection of their life, health and safety. The research method consists in a survey that gave, to a number of 560 credit beneficiaries, qua consumers, the opportunity to freely express their viewpoints. Data collection and processing has resulted in the filling of a 14 queries questionnaire by each of the 560 consumers in the South-Western Oltenia region and, subsequently, in data analysis. The main findings show that consumers have experienced a decline in what concerns their standard of living and that sustainable consumption of goods was barely stimulated. Based on the survey results, the paper proposes a banking accountability indicators system and a consumer credits quality pattern of analysis that would increase banking accountability towards such credits by reducing their negative externalities on people’s lives, stimulating sustainable consumption, giving thorough and accurate information, managing complaints and disputes, educating and raising consumers awareness.